Evaluation and development of passion fruit (Passiflora alata Dryander) propagated by cutting and seet in conditions of commercial orchard - Roncatto, Givanildo; Nogueira Filho, Geraldo Costa; Ruggiero, Carlos [UNESP]; de Oliveira, Joao Carlos [UNESP]; Geraldo Martins, Antonio Baldo [UNESP] (Soc Brasileira Fruticultura, 2008)
The present work was conducted in a fruit tree propagation area of the Plant Production Department of the Faculdade de Ciencias Agrarias e Veterinarias, Universidade Estadual Paulista (FCAV/UNESP) in Jaboticabal, SP, and also in a commercial orchard in Araguari, MG, with the objective to verify the potential of vegetative growth (stem diameter, height of plants and leaf number) of plants of passion fruit (Passiflora alata Dryander), gotten by cutting and seed, comparing the initial development of plants in the field. This experiment was carried out from January 2002 to February 2003. The experiment using seeds was conducted at a shadow house, and the one that used cuttings in an intermitent mist. The cuttings and seeds were collected from adult plants which came from Passifloraceae Active Germoplasm Bank (BAG) of the Plant Production Department of FCAC/UNESP. For the cuttings, it was used the intermediate part of the branches in stadium of vegetative growth. The seeds, in order to obtain the seedlings, had been sown in plastic trays. Cuttings and seedlings were transplanted to plastic bags with substrate in shadow house and with daily irrigation. They were acclimatized and planted on field, after 60 days. on field, the stem diameter, plant height and number of leaves were better for cuttings than for seedlings in Jaboticabal, SP. In Araguari, MG, stem diameter was larger in the seedlings, which plant heights and number of leaves were larger on cuttings.
Keywords: Rootstock; Growth; Diameter; plant height and number of leaves